Influence of African-American music on Montage of a Dream Deferred by Langston Hughes - Ročňák, Lukáš (Univerzita Pardubice, 2015)
This thesis acquaints readers with the profound influence of African-American music on the poetry of Langston Hughes, more specifically on his poem suite Montage of a Dream Deferred from 1951. The theoretical part provides information about Hughes' cultural background that is inextricably associated with the Harlem Renaissance. Then, basic characteristics and techniques of his poetry are briefly outlined. The development of individual African-American musical forms is discussed. Authors and artists that heavily influenced Hughes are introduced. Afterwards, typical poetic devices and linguistic features of blues and jazz poetry are highlighted for use in the ensuing analysis. The following part thoroughly scrutinizes African-American music elements of eight selected poems from Montage of a Dream Deferred. Subsequently, Hughes' enduring impact is concisely elucidated. Lastly, the results are addressed in the final chapter.
Influence of African-American music on Montage of a Dream Deferred by Langston Hughes
Keywords: Hughes, Langston; Harlem; blues; jazz; influence; montage; music; poetry; vliv; montáž; hudba; poezie